Comparative study of assortment of medical films presented in the pharmaceutical markets of Ukraine, USA and Poland - M. B. Demchuk; T. A. Groshovyi; N. V. Malanchyk (The State Expert Center of the Ministry of Health of Ukraine, 2020)
The development of medical films containing active substances immobilized on polymeric carriers become significantly popular in the world. Medical films belong to the application forms and designed for injection of active pharmaceutical ingredients through the skin, periodontal tissue, the mucous membrane of the mouth. There are transdermal therapeutic systems, including buccal, dental and oral films. Pharmaceutical manufacturers present a wide range of medicinal films containing various active ingredients on the world market. The purpose of our study was to conduct a comparison of the range of medicines in the form of medical films registered in the pharmaceutical markets of Ukraine, USA, and Poland. The object of the study was information on registered drugs in Ukraine, the USA, and Poland. The applied methods of study include generalization, systematization, and comparative analysis. The range of medicinal films presented in the pharmaceutical markets of Ukraine, the USA, and Poland is analyzed. It is found that as of November 2019, there were 24 medicinal films registered in Ukraine, 70 medicinal films in Poland, and 104 medicinal films in the USA. Medicines in the form of transdermal therapeutic systems or patches have been registered in the pharmaceutical market of Ukraine. No buccal and oral drug films have been registered. In the Ukrainian market medicinal films are exclusively represented by foreign manufacturers from Germany (65%), Ireland (10%), Belgium (10%), Greece (5%), United Kingdom (5%), and the United States (5%). The largest range of medical films is presented in the USA: 89.2% transdermal films, 7.8% - buccal films, 2.9% - oral films. In the Polish market, transdermal therapeutic systems also account for the largest share, with only 3% of the range being buccal films. In this study, we found that the active substances such as fentanyl, buprenorphine, estradiol, nicotine, nitroglycerin, rivastigmine, rotigotine, testosterone, scopolamine, oxybutynin, and others are most often introduced into drug films. It is found that in the US market the share of domestic manufacturers of medical films is 55.79%. Ukrainian pharmaceutical manufacturers do not offer medical films, which is a prerequisite for the development of those domestic dosage forms.